Determinants of stunting among children aged 6-59 months at Kindo Didaye woreda, Wolaita Zone, Southern Ethiopia: Unmatched case control study - Batiro, Bancha; Demissie, Tsegaye; Halala, Yoseph; Anjulo, Antehun Alemayehu (PLOS ONE, 2017)
Background Stunting is a well-established risk marker of poor child development. Globally in 2017, 155 million children under 5 were estimated to be stunted. While different activities are being done to reduce the burden of stunted growth, the problem is overwhelming in Africa; it was increased by 24%. Therefore, identifying determinants of stunting among children aged 6–59 would help to set priorities for action and to the design of stunting reduction plan at a grassroots level. Methods The unmatched case-control study was conducted in randomly selected 8 rural kebeles of Kindo Didaye woreda, Ethiopia from February to April, 2016 to identify the determinants of stunting among children aged 6–59 months. The sampling frame was identified by enumeration of 6–59 months of age children in the entire households of the study area. From which 155 as cases and 310 as controls were chosen using anthropometric measurement based on the median of WHO 2006 reference population. The anthropometric data were analyzed by WHO Anthro 2010 software to generate Z-score values. Odds Ratio along with 95% confidence interval was estimated to identify determinants of stunting using the multivariable logistic regression. Results Drinking water from unsafe source (AOR = 7.06, 95% CI; 4.40–20.42),occasionally eating animal source food (AOR = 0.51, 95% CI; 0.02–0.68), ARI in the past two weeks (AOR = 3.04, (95% CI; 1.04–13.35), late initiation of breastfeeding after one hours after birth (AOR = 5.16, 95% CI; 2.24–15.90) and lack of vaccination (AOR = 6.38, 95% CI; 2.54–17.10)were significantly associated with stunting. Conclusions Factors like exposure to diarrhea disease, exposure to acute respiratory infection, late initiation of breast milk after child breath, squeeze out of 1st breast milk, lack of vaccination, animal source of food, and unsafe source of water for drinking could be used to set priorities for action and to the design of Kindo Didaye woreda plan for stunting reduction down to grassroots level. Therefore, zonal health department and Kindo Didaye woreda health office should promote the importance of colostrums feeding. Drinking water should be decontaminated. Expansion of vaccination program to enhance herd immunity at the community level is important.